Epidemiological analysis of hospitalizations for migraine and other headache syndromes in southern Brazil between 2019 - 2023 - Caetano, Maria Clara Calixto; Brandão, Brenda Lopes; Boreggio, Hugo Berdejo; Silva, Júlia Esteca da; Schuch, Karolina Lemos; Stetter, Letícia Loreta Roque; Oliveira, Lorena Pedro de; Mota, Nicolas França; Silva, Celijane Almeida (Headache Medicine, 2024)
Introduction: Migraine is a disease primarilycharacterized by pulsating headaches of moderate tosevere intensity, often accompanied by othersymptoms such as nausea, vomiting, and sensitivityto light and sound. Migraine is a common complaint, with Brazil reporting a total of 51,269 hospitalizationsdue to migraines and other headache syndromes. The Southern region of Brazil accounted for 25.86% of the recorded cases, totaling 13,260 hospitalizations from 2019 to December 2023. Objective: To map the epidemiological profile ofhospitalizations in the Southern region of Brazil from2020 to 2023. Methodology: This ecological, descriptive, retrospective study utilized data from theDepartment of Informatics of the Unified Health System (DATASUS) of the Ministry of Health, collected from January 2019 to December 2023. Results: The total number of individuals hospitalizedfor migraine and other headache syndromes in theSouthern region was 13,260, with 2019 having thehighest number of hospitalizations (4,017) and 2021 the lowest (1,771). Women were the most affected, representing 65% (8,566) of cases, while menaccounted for 35.4% (4,694). The predominant age group was 40 to 49 years, with 17.37% (2,303) ofcases reported, and the least affected age group wasunder 1 year, with 0.13% (17) cases reported. The white race accounted for 81.25% of reported cases. Conclusion: Analyzing the epidemiological profile ofthe population residing in the Southern region ofBrazil hospitalized for migraine and other headachesyndromes between 2019 and 2023 reveals that2019 had the highest number of hospitalizations. The most affected age group was 40 to 49 years, andwomen were the most impacted gender. The mostaffected ethnicity was white. Therefore, elucidatingthe specific epidemiological patterns of this region isvital for implementing appropriate and individualizedhealthcare measures.